African trade in livestock products and value chains - Kurtz, Julie E.; Mitik, Lulit; Zaki, Chahir (AKADEMIYA2063, 2021)
[This] chapter has several objectives. First, we examine the main trade flows (by product and by destination and origin markets) for the three product groups of interest, with some focus on informal trade. Next, we investigate the protectionist effect of trade policies, tariffs, and NTMs. Then, we consider the opportunities and risks in livestock production systems, especially risks from climate change and conflict, which are the primary threats to food security in Africa (IFPRI 2019). In the final section, we conclude and offer some recommendations.